Examining the Influence of Heart Disease Risk Factor Knowledge and Social Support in African American Women - Brittny Bratcher-Rasmus; Marilyn Massey-Stokes; Mandy Golman; Ann Amuta; Dwalah Fisher; Keisha Johnson (Health Behavior Research, 2024)
Heart disease disproportionately impacts African American women and disparities can stem from risk factors related to limited risk factor knowledge and socioeconomic resources. Social support mitigates heart disease risk in this population. The study aimed to examine how perceived social support impacts heart disease risk factor knowledge among African American women and whether demographic characteristics moderate a relationship between perceived social support and heart disease knowledge. This was a quantitative study with purposeful, snowball sampling representative of African American women aged 30-55 in Texas (n = 121) who completed an online survey on heart disease knowledge and perceived social support. Approximately half the participants displayed heart disease knowledge deficiencies. Multiple regression analysis revealed that when demographic variables were controlled, age (standardized β= .28, p = .002) and income (standardized β= .19, p = .037) were the only predictor variables indicating that social support impacts heart disease knowledge, with nonsignificant differences in the regression model (standardized β = -.023, p = .80). Hierarchical multiple regression revealed that age (F change = 1.056, R square change = .008, and p = .306), education (F (3, 115) = .583, p = .627), family history (F (2, 116) = 1.51, p = .225), and income (F change = 1.006, R2 change = .008, and p = .318) as individual predictors yielded nonsignificant differences in the overall predictive model, indicating demographic variables did not moderate a relationship between social support and heart disease knowledge. Social support is critical to decision-making and lifestyle modifications, which can protect against chronic diseases such as heart disease in African American women. Further understanding of the connection between perceived social support and heart disease knowledge through public health education programs can be instrumental in reducing heart disease disparities among African American women.